Redefining the link between subjective norm and entrepreneurship intention: mediating effect of locus of control / Nurul Hidayana Mohd Noor, Mahazril 'Aini Yaacob and Noralina Omar - Mohd Noor, Nurul Hidayana; Yaacob, Mahazril 'Aini; Omar, Noralina (Faculty of Business and Management, 2021)
Entrepreneurship acts as a panacea for improving country growth and is prevalent in reducing the unemployment rate. A plethora of studies have focused on the main determinants that affect people's intention to become an entrepreneur. The entrepreneurship intention research is mainly focused on the influence of the external environment and the individual personality aspects are not sufficiently considered. This study examines the mediating effect of locus of control in the relationship between subjective norm and youth entrepreneurship intention. This study is based on a cross‐sectional online survey design. The sample includes 248 Malaysian youth. The variables are measured based on the adapted scales and IBM SPSS 27 was used for the statistical analysis. Data were analysed using regression analysis to assess the possible mediating effect of locus of control. The present study provides evidence that locus of control partially mediates the relationship between subjective norm and entrepreneurship intention. Thus, this study concluded how entrepreneurs differ from the rest of the population in terms of locus of control. This study contributes to entrepreneurship literature by revealing that individuals with a high internal locus of control are more likely to become entrepreneurs.